An iterative Algorithm for Hemicontractive Mappings in Banach Spaces - Youli Yu; Zhitao Wu; Pei-Xia Yang (Abstract and Applied Analysis)
We First introduce a three-step iterative algorithm for approximating the fixed points of the hemicontractive mappings in Banach spaces. Consequently, we prove the strong convergence of the proposed algorithm under some assumptions. Since three-step iterations include Ishikawa iterations as special cases, our result continue to hold for these problems. Our main results can be viewed as an important refinement of the previously known results.